There was an old lady who swallowed a fly - Taback, Simms (New York : Viking, 1997)
Ever-expanding die-cut holes show exactly what is happening in the old lady's stomach as she swallows an assortment of creatures, beginning with a small fly, and ending with a fatal horse.
On die-cut pages.
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Booklist, November 1997.
Bulletin (Center for Children's books), March 1998.
Keywords: Folk songs, English -- Texts; Toy and movable books -- Specimens; Folk songs; Nonsense verses; Toy and movable books; English folk songs; Nonsense verses; Toy and movable books